HISTOLOGICAL CHANGE IN LIVER OF A FISH LABEO ROHITA (HAM.) DUE TO CADMIUM - SINGH, ARUN KUMAR; RANA, K.S.; SOLANKI, SUNITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2006)
Histological changes were observed in the liver of fish due to cadmium exposure. Histopathological effects of cadmium were proportionately greater in fishes exposed to higher concentration of cadmium, although the effects of even at lower concentration, were not insignificant. The present paper describes the histological changes in the liver of Labeo rohita (Ham.) due to cadmium.